Adiposity may predict survival in patients with advanced stage cancer treated with immunotherapy in phase 1 clinical trials. Issue 3 (24th October 2019) - Martini, Dylan J.; Kline, Meredith R.; Liu, Yuan; Shabto, Julie M.; Williams, Milton A.; Khan, Amir Ishaq; Lewis, Colleen; Collins, Hannah; Akce, Mehmet; Kissick, Haydn T.; Carthon, Bradley C.; Shaib, Walid L.; et al.
Abstract : Background: Body mass index (BMI) is used to define obesity, but it is an imperfect measure of body composition. In the current study, the authors explored the association between types of fat and survival in patients treated with immunotherapy. Methods: A retrospective analysis of 90 patients who were treated with immunotherapy on phase 1 clinical trials at the Winship Cancer Institute in Atlanta, Georgia, from 2009 through 2017 was performed. Overall survival (OS) and progression‐free survival (PFS) were used to measure clinical outcomes. Baseline BMI and radiographic images at the middle of the third lumbar vertebrae were obtained. Fat densities were calculated and converted to indices (subcutaneous fat index [SFI], intermuscular fat index [IFI], and visceral fat index [VFI]) after dividing by height in meters squared. Risk groups were created using recursive partitioning and the regression trees method for SFI and IFI, which were selected by stepwise variable selection among all fat‐related variables. The Cox proportional hazards model and Kaplan‐Meier method were used for the association with OS and PFS. Results: The majority of patients (59%) were male and diagnosed with melanoma (33%) or gastrointestinal cancers (22%). The median BMI was 27.4 kg/m 2, the median SFI was 62.78, the median IFI was 4.06, and the median VFI was 40.53. Low‐risk patients (those with an SFI ≥73) had a significantly longer OS (hazard ratio, 0.20; 95% CI, 0.09‐0.46 [ P < .001]) and PFS (hazard ratio, 0.38; 95% CI, 0.20‐0.72 [ P = .003]) compared with patients at intermediate risk (those with an SFI <73 and IFI <3.4) and poor risk (those with an SFI <73 and IFI ≥3.4). The Uno concordance statistics were found to be higher for fat risk groups than BMI in predicting OS (0.603 vs 0.574; P = .581) and PFS (0.602 vs 0.586; P = .71). Conclusions: Increased BMI, increased SFI, and decreased IFI may be associated with prolonged survival in patients with cancer who are treated with immunotherapy. Further studies are needed to elucidate the effect of adiposity on the host immune response to immunotherapy. Abstract : In the current study, the authors have created a novel risk scoring system that appears to be significantly associated with survival in patients with cancer who are treated with immunotherapy in phase 1 clinical trials. This study is important for practicing oncologists because the authors have provided clinically relevant cutoff values for subcutaneous and intermuscular fat indices that may be used to risk stratify patients who are treated with immunotherapy.